Changes in the adoption of the components of coffee berry borer Hypothenemus hampei (Coleoptera: Scolytidae) integrated management, through participative methodologies - ARISTIZÁBAL-A., LUIS FERNANDO; SALAZAR-E., HUGO MAURICIO; MEJÍA-M., CARLOS G. (Revista Colombiana de Entomología, 2002)
Since July of 1998, the Entomology Discipline of Cenicafe, the Common Fund for Commodities (CFC), and CABI-BioScience have been carrying out a participative research project in Colombia that involves small coffee growers with the aim to improve the adoption of coffee berry borer management practices (CBBMP). The results showed that the coffee growers have improved the efficiency and adopted all the practices related to the coffee berry borer management that were evaluated. The Re - Re practices to control CBB were used by 98% of the growers. They recognized them as the most important way of CBBMP. The insecticide applications showed a sharp decrease from 80 to 42% and the growers changed the application system from spraying the full plantation to applications only in spots with a high infestation of CBB. To make insecticides application they rely on previous evaluations of CBB infestation. The monitoring practices to manage CBB field population also showed a tremendous change from 15 to 80%. Respect to the biological control (entomopathogenic fungus and parasitoids). their use and acknowledgment experienced a sharp increase in adoption and changed from 18 to 81 %. The postharvest CBB also changed from 7 to 82%. As a conclusion to this evaluation the coffee growers said that when the work is done "Leern Doinq" it contributes to understanding the "why", and it also increases the self-esteem and the level of participation. It also encourages the generation of ideas and facilitates the adoption of technology.